(untitled) (Global Journal of Human-Social Science, 2020)
This article is part of an extensive research project that aims to verify the particularities of social and economic development in Latin America in the late 20th and early 21st centuries We work with the hypothesis that although the countries of the Latin American continent present different degrees of development their economies still remain linked to a type of external regulation that induces them to believe in the possibilities of development without however reversing the levels of dependence on the countries of central capitalism It is therefore an ideology of development that enables topical occasional and specific advances but does not overcome the economic and political subordination of the Latin America In this article we present the two main assumptions of the research firstly we explain what we mean by development ideology and secondly we summarize some aspects that demonstrate how development ideology is expressed in Latin America in the late 20th and early 21st centuries through diversified economic regulation processes